1998
DOI: 10.1292/jvms.60.989
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Neonatal Rat Ductal Responsiveness to Prostaglandin E2 after Maternal Treatment with Enalapril or Captopril.

Abstract: ABSTRACT. This work was conducted to determine whether the angiotensin-converting enzyme inhibitors (ACEIs) (enalapril and captopril) administered to mother rats prenatally can potentiate a re-opening of the neonatal ductus arteriosus (DA) induced by prostaglandin E 2 (PGE 2 ) after postnatal closure. A subcutaneous injection of PGE 2 (4 µg) was administered to newborn rats 3 hr after a Cesarean delivery from females which had been orally given 0.1, 1 or 10 mg/kg/day of enalapril or 15 or 150 mg/kg/day of capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…However, prenatal exposure to ACEIs might inhibit ductal closure via the effects of ACEIs on the fetal bradykinin-prostaglandin system [10]. The present study also supports the view that ACEIs such as enalapril inhibit the maturation of the DA, and that the DA responsiveness to PGE2 thereby increased [30], and this mechanism may be partly responsible for the development of PDA, because PDA often occurs in immature infants [8].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, prenatal exposure to ACEIs might inhibit ductal closure via the effects of ACEIs on the fetal bradykinin-prostaglandin system [10]. The present study also supports the view that ACEIs such as enalapril inhibit the maturation of the DA, and that the DA responsiveness to PGE2 thereby increased [30], and this mechanism may be partly responsible for the development of PDA, because PDA often occurs in immature infants [8].…”
Section: Discussionsupporting
confidence: 82%
“…The use of ACEIs during the second and third trimesters of pregnancy has been associated with fetal and neonatal morbidity, including intrauterine growth retardation, oligohydramnios, reversible and irreversible renal failure and patent ductus arteriosus (PDA) [2,23]. In a previous study, we suggested that the use of ACEIs may cause PDA based on the observations that re-opening activity of the DA increased significantly after maternal treatment with enalapril or captopril [30] and spontaneous closure of the DA was partly inhibited after treatment with enalapril [28,29]. However, prenatal exposure to ACEIs might inhibit ductal closure via the effects of ACEIs on the fetal bradykinin-prostaglandin system [10].…”
Section: Discussionmentioning
confidence: 99%